2019
DOI: 10.1016/j.yjmcc.2019.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular inflammation: RNA takes the lead

Abstract: Inflammation has recently gained tremendous attention as a key contributor in several chronic diseases. While physiological inflammation is essential to counter a wide variety of damaging stimuli and to improve wound healing, dysregulated inflammation such as in the myocardium and vasculature can promote cardiovascular diseases. Given the high severity, prevalence, and economic burden of these diseases, understanding the factors involved in the regulation of physiological inflammation is essential. Like other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 145 publications
(175 reference statements)
0
15
0
Order By: Relevance
“…In a study by Vickers et al, miR-222 level in circulating HDL was found to be 8.2-fold higher in familial hypercholesterolemia patients compared with HDL from normal subjects 64) . miR-222 regulates insulin sensitivity, and miR-222 levels are higher in plasma of obese human patients 70) .…”
Section: Shear Stress-induced Pcsk9 Expressionmentioning
confidence: 91%
See 1 more Smart Citation
“…In a study by Vickers et al, miR-222 level in circulating HDL was found to be 8.2-fold higher in familial hypercholesterolemia patients compared with HDL from normal subjects 64) . miR-222 regulates insulin sensitivity, and miR-222 levels are higher in plasma of obese human patients 70) .…”
Section: Shear Stress-induced Pcsk9 Expressionmentioning
confidence: 91%
“…To clarify its role in atherosclerosis and its reason for existence, further research is required. production 63,64) .…”
Section: Shear Stress-induced Pcsk9 Expressionmentioning
confidence: 99%
“…MicroRNAs affect gene expression, and their dysregulation increases inflammation and leads to atherosclerosis [11][12][13]. Studies have shown that many microRNAs, including miR-504, -200, -138 and -210, regulate the proliferation and migration of VSMCs [3].…”
Section: Introductionmentioning
confidence: 99%
“…In deed, the regulation of miRNAs with specific genes in cells can modulate specific biological pathways. The extensive dysregulation of miRNA expression may reflect multiple cellular defense responses caused by inflammation, bacterial infections, and viral infections [34][35][36]. Upon viral infection, the host can alter several specific biological pathways, such as differentiated growth, development, apoptosis, changes in metabolic pathway, and homeostasis.…”
Section: Discussionmentioning
confidence: 99%